Bubble‐pen lithography: Fundamentals and applications: Nanoscience: Special Issue Dedicated to Professor Paul S. Weiss. Issue 4 (8th March 2022) - Kollipara, Pavana Siddhartha; Mahendra, Ritvik; Li, Jingang; Zheng, Yuebing
Abstract: Developing on‐chip functional devices requires reliable fabrication methods with high resolution for miniaturization, desired components for enhanced performance, and high throughput for fast prototyping and mass production. Recently, laser‐based bubble‐pen lithography (BPL) has been developed to enable sub‐micron linewidths, in situ synthesis of custom materials, and on‐demand patterning for various functional components and devices. BPL exploits Marangoni convection induced by a laser‐controlled microbubble to attract, accumulate, and immobilize particles, ions, and molecules onto different substrates. Recent years have witnessed tremendous progress in theory, engineering, and application of BPL, which motivated us to write this review. First, an overview of experimental demonstrations and theoretical understandings of BPL is presented. Next, we discuss the advantages of BPL and its diverse applications in quantum dot displays, biological and chemical sensing, clinical diagnosis, nanoalloy synthesis, and microrobotics. We conclude this review with our perspective on the challenges and future directions of BPL. Abstract : We review a laser‐based bottom‐up fabrication technique called bubble‐pen lithography (BPL), which exploit optothermally controlled bubble to print, pattern, or synthesize various materials (i.e., micro/nanoparticles, organisms, molecules) on substrates. Recent advances in fundamental understanding and technological development of BPL are discussed along with its applications in various fields. The review concludes with our perspective on the challenges and future opportunities of this emerging technology.